Points of exclusion: Black Caribbean and South/Southeast Asian international student graduates navigating structural barriers in the Canadian Express Entry System - Ellis, Everton (Journal of International Students, 2026)
Since the 2010s, Canada’s federal and provincial governments have introduced immigration and labor policies to compete in the global race for skilled talent, including international student graduates (ISGs). This paper shows that Canada’s color‑blind immigration framework produces discriminatory and structural barriers for Black Caribbean and South/Southeast Asian ISGs navigating post‑graduation pathways to permanent status. It reveals intersectional inequities within the Express Entry System for skilled workers, including ISGs. The respondents’ transcripts highlight oppressions tied to age, marital status, immigrant “otherness,” and gender identity, alongside structural barriers such as repeated language testing, intense competition, and the randomized or opaque nature of the Comprehensive Ranking System (CRS) draw process. These factors shape their immigration outcomes. The paper concludes that the opacity of the Express Entry selection mechanism illustrates how race-neutral policy discourse masks racialized logics of exclusion embedded in immigration policies that reproduce systemic inequities while presenting themselves as objective and merit-driven.